Transylvania - Von Finn, Denny (Minneapolis, Minnesota : Bellwether Media, Inc., 2013)
"Engaging images accompany information about Transylvania. The combination of high-interest subject matter and light text is intended for students in grades 3 through 7"--
Includes bibliographical references and index.
Keywords: Haunted places -- Romania -- Transylvania -- Juvenile literature; Vampires -- Romania -- Transylvania -- Juvenile literature; Transylvania (Romania) -- Miscellanea -- Juvenile literature